Magnetically-Modulated Atomic Force Microscopy for Analysis of Soft Matter Systems - Kageshima, Masami (Current Pharmaceutical Biotechnology, 2012)
Experimental method of studying viscoelasticity, a common idea to understand properties of microscopic biological soft matter systems, especially single biopolymer chains, using atomic force microscopy (AFM) with magnetically- driven cantilever is surveyed. The experimental setup of applying well-characterized excitation to the cantilever and the analysis method to derive the viscoelasticity of the system under study are briefly introduced. Examples of measuring viscoelasticity of single peptide molecule and single titin molecule are shown. Considering the close relation of viscoelasticity and the time-scale for nonequilibrium dynamics in soft matter, extension of the method to a frequency-resolved analysis is attempted. A result of measuring viscoelasticity spectrum of a single dextran chain is shown. Challenges in further progress of the method are also described.
Keywords: viscoelasticity